Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jfpp.15512
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the extraction of antioxidants from Moringa leaves: A comparative study between ultrasound‐ and ultra‐homogenizer‐assisted extractions

Abstract: As the demand for healthier foods increases, the use of synthetic antioxidants in the food industry has been the subject of questions regarding food safety due to toxicity issues. Several researches are focused on the search for natural compounds that exhibit this functional property and many plant matrices were studied as potential sources of antioxidants (Cañadas et al., 2021;Fombang et al., 2020;Kumar et al., 2021;Santos et al., 2021). To obtain the antioxidants from plant matrices, the optimization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…These conditions are similar to those reported by [13], 60 min and 60 °C, and by [18] 3). [14,21] to maximize the extraction of flavonoid compounds were 5 and 15 min, respectively; these values are lower than those reported to maximize the extraction of phenolic compounds of 42 and 60 min in other studies [13,18].…”
Section: Evaluation Of Abtscontrasting
confidence: 70%
See 1 more Smart Citation
“…These conditions are similar to those reported by [13], 60 min and 60 °C, and by [18] 3). [14,21] to maximize the extraction of flavonoid compounds were 5 and 15 min, respectively; these values are lower than those reported to maximize the extraction of phenolic compounds of 42 and 60 min in other studies [13,18].…”
Section: Evaluation Of Abtscontrasting
confidence: 70%
“…This result is greater than the value of 13.4 mg GAE/g of total phenolic found in extract of leaves of M. oleifera collected in Italy by using an optimization by UAE [13]. In another study done in Brazil was reported concentrations up to 26.6 mg GAE/g using UAE technology in M. oleifera leaves [14]. In Mexico, was obtained around 12 mg GAE/g of an extract of phenolic compounds from M. oleifera leaves [2].…”
Section: Evaluation Of Abtsmentioning
confidence: 57%
“…The total phenolic content of M. oleifera leaves extract was 1333.84 mg GAE/ml of dry weight and showed a concentration dependent DPPH radical‐scavenging activity with EC 50 of around 12.43 mg extract/ml. Pereira et al (2021) reported similar values of total phenolics in their work with M. oleifera extract using ultrasound and ultra‐homogenizer extraction.…”
Section: Resultsmentioning
confidence: 56%
“…Because of the very high pressure, cell damages occur, which in turn can result in improved extraction performances. Both HHP and PEF have already been used in extraction procedures for grapes ( 31 ), moringa ( 32 ), red cherries ( 33 ), tea leaves ( 34 ), ginger ( 34 ), and tomatoes ( 35 ). The improvement of citrus juice quality was the focus of earlier investigations on the effects of the PEF or HHP procedure ( 36–38 ), whereas the citrus peel was sparingly handled and evaluated to optimize the aforementioned extraction techniques ( 39 ).…”
Section: Introductionmentioning
confidence: 99%